Cross domain fault diagnosis of small modular reactor using sample synthesis and transfer learning with attention mechanism - Run Luo; Xiangcheng Pan; Yadong Li; Yang Liu; Hongtao Wan; Shun Hu; Tao Yu; Chao Xie (Annals of Nuclear Energy, 2026)

Bacterial co-culture significantly enhanced polyethylene biodegradation - Qiang Liu; Yuzhi Sun; Pen Jin; Liang Shen; Run Hu; Lisha Song; Yanjiao Qi; Zhenbin Chen; Hong Zhang (Journal of Environmental Chemical Engineering, 2026)

Ex-situ catalytic microwave-assisted gasification of sewage sludge over Ni-modified MIL-100 (Fe) derived catalysts: Tar reforming for hydrogen-rich syngas - Mingtao Hu; Huiwen Wu; Wenyi Deng; Lingyu Tai; Xuerong Zheng; Weihao Li; Yaxin Su; Run Xu (Journal of Environmental Chemical Engineering, 2026)

Insights into the regulatory role of pulsed electric field-induced ROS burst in metabolite changes during potato processing: Integrated transcriptomic and metabolomic analysis - Renjie Zhao; Qiannan Liu; Jing Li; Run Shi; Ruixuan Zhao; Honghai Hu (Food Chemistry, 2026)

Integrated Heart Rate Monitoring and Transcriptomic Analyses Reveal Distinct Responses to Hypo- and Hypersalinity Stress in Abalone - Nan Chen; Run Hu; Yun Chen; Weiwei You; Caihuan Ke; Yawei Shen (Fishes, 2026)
In the context of global climate change, intensified salinity fluctuations driven by altered precipitation, extreme rainfall events, and typhoons have emerged as a major threat to coastal mollusk aquaculture. In this study, integrated physiological and transcriptomic analyses were performed to investigate the responses of Pacific abalone (DD, Haliotis discus hannai) and its hybrid (DF, H. discus hannai ♀ × H. fulgens ♂) to hypo- and hypersalinity stress. Two salinity breakpoints (BPS1 for hyposalinity, BPS2 for hypersalinity) were identified using heart rate monitoring to indicate the osmotic tolerance thresholds of the abalone. The BPS1 and BPS2 values did not differ significantly between the DD and DF groups. However, a subsequent 30-day culture trial confirmed that exposure to the salinity level corresponding to BPS1 significantly reduced growth and survival of both DD and DF groups. To explore the molecular mechanisms underlying these two salinity breakpoints in abalone, the transcriptomes of hemocytes and gill tissues were profiled under both stress conditions. Both hypo- and hypersalinity stress induced pronounced transcriptomic responses in abalone, accompanied by upregulated differentially expressed genes (DEGs) significantly enriched in pathways like TNF and NF-κB signaling, including genes like piap, diap2, birc7-a, birc2, and birc3. However, abalone exhibited more intense responses to hypersalinity stress, as reflected by a greater number of annotated differentially expressed genes (DEGs) and more complex transcriptional regulation. Overall, this study integrates physiological assessment based on heart rate monitoring, aquaculture trials, and transcriptomic analysis to advance our mechanistic understanding of osmotic stress adaptation in abalone, while laying a scientific foundation for the sustainable development of abalone aquaculture under global climate change.

Per- and polyfluoroalkyl substances in food contact materials: Migration, health risks and sustainable alternatives - Run Li; Shensheng Xiao; Jiayong Hu; Qiao Wang; Jingguang Li; Min Fang; Nannan Qiu; Xin Liu; Yongning Wu (Trends in Food Science & Technology, 2026)

High-thermopower ionic thermoelectric hydrogel with gradient immobilization of anions by polypyrrole - Zhou Li; Wenzhuo Zhao; Shouze Li; Dongyan Xu; Wonjoon Choi; Run Hu (Chemical Engineering Journal, 2026)

Uncertainty quantification and physical information learning for safe measurement of resonant flowmeters in multiphase flow: A Bayesian approach with physically-constrained residual injection - Ziwei Yang; Haibo Liang; Run Jiang; Mingyang Liu; Deshen Li; Jie Liu; Jingwen Hu (Process Safety and Environmental Protection, 2026)

Remediation strategies of plastics contaminated soils based on novel bacterial communities: Enhancing plastic degradation and element cycling - Qiang Liu; Yuzhi Sun; Pen Jin; Liang Shen; Run Hu; Lisha Song; Yanjiao Qi; Zhenbin Chen; Hong Zhang (Chemical Engineering Journal, 2026)

Tissue Tropism and Pathogenesis of LMBV in Largemouth Bass: A Comparative Study of Injection and Immersion Infection Models - Tianmei Hu; Dingzhe Zou; Baozhou Wu; Haiyue Chen; Shuguang Hao; Ying Tian; Wangqian Xu; Yifei Li; Jie Zhou; Run Yang; Jiping Zhang; Yu Liu; et al. (Journal of Fish Diseases, 2026)
Largemouth bass ranavirus (LMBV) poses a significant threat to the aquaculture industry by causing severe systemic disease and substantial economic losses. This study investigates the tissue distribution, pathological damage, and host response following LMBV‐GD1909 infection using two infection models: experimental injection and simulated natural immersion. In the injection model, infected fish exhibited clinical signs, including skin ulcers, haemorrhaging at fin bases, body darkening and organ swelling. Histopathological analysis revealed extensive multi‐organ damage, particularly in the liver, spleen, and kidney, characterised by necrosis, haemorrhage, vacuolar degeneration and inflammatory infiltration. Haematological and serum biochemical analyses indicated significant alterations in key parameters, including elevated WBC, RBC and GLU levels, and reduced PLT, TP and LDH levels, reflecting systemic physiological disruption. Viral dynamics analysis demonstrated the pantropic nature of LMBV, with rapid dissemination to multiple tissues post‐injection. The liver and spleen were identified as primary target organs, showing the highest viral loads and most severe pathology, indicating a direct correlation between viral load and organ dysfunction. In the immersion model, simulating natural infection, the gills and skin displayed the highest viral loads initially, identifying them as the major entry portals. The gills also served as a key site for viral replication, with a clear gradient of viral spread from external to internal tissues observed over time. This study comprehensively elucidates the tissue tropism, dissemination pathways, and pathological impact of LMBV, providing critical insights for developing targeted prevention and control strategies against LMBV.

The remediation effect of C/N cycling driven by the synergistic interactions of functional strains and straw in poly(butylene adipate-co-terephthalate)-contaminated soil - Hong Zhang; Lisha Song; Run Hu; Huan Liu; Yaohua Shi; Qiang Liu; Yanjiao Qi (Journal of Environmental Sciences, 2026)

A novel wind–solar integrated scenario generation method considering seasonal characteristics - Zhen Zhang; Hui-Min Zuo; Jian-Yong Hu; Ling-Hua Wang; Run-Long Zhang (Theoretical and Applied Climatology, 2026)

RNA interference with the selenoprotein M gene inhibits the growth promoting effect by selenium supplementation to silkworm Bombyx mori - Run-Hui Ma; Wen-Jie Ge; Fei Hu; Ting-Ting Hong; Kiran Thakur; Shun-Ming Tang; Zhao-Jun. Wei (Journal of Asia-Pacific Entomology, 2026)

Kerogen-driven synergistic interactions in oil shale and microplastics co-pyrolysis: mechanistic insights into product distribution and oil upgrading - Shuai Li; Erfeng Hu; Guangwen Xu; Jianglong Yu; Haifeng Gong; Zuohua Liu; Guocan Zheng; Run Dong; Fan Xu (Chemical Engineering Journal, 2026)

An unprecedented alternariol-zinnol hybrid and six undescribed zinnol derivatives from the phytopathogen Alternaria solani and their cytotoxic activities - Ming Hu; Run-Cheng Yan; Qiao-Ling Wei; Jiang-Li Su; Bi-Juan Yang; Wen-Chao Tu; Gan-Peng Li; Xing-De Wu (Phytochemistry, 2026)

Pyrogenic carbon-stimulated nitrate-dependent anaerobic methane oxidation: insights into redox activity and conductivity in anaerobic methanotrophic archaea metabolism and microbial dynamics - Fangrui Cai; Yu Wang; Mengying Xie; Guanbin Li; Suicao Wang; Venea Dara Daygon; Dihua Tian; Gaofeng Ni; Xiang Liu; Run Zhang; Lirong Lei; Zhiguo Yuan; et al. (Water Research, 2026)

Effect of air frying, oven baking, pan frying, and deep frying on flavor profile and acrylamide formation in reheated hash browns - Run Shi; Qiqi Mi; Renjie Zhao; Qiannan Liu; Jing Li; Wei Liu; Ruixuan Zhao; Honghai Hu (Food Chemistry, 2026)

Target Fibroblast-B cell crosstalk via MIF signaling drives pathogenic B cell differentiation and joint damage in knee osteoarthritis - Bizhi Tu; Zheng Zhu; Yan Li; Zhengming Zhu; Shijie Wang; Peizhi Lu; Ya Li; Shuo Yang; Dingtao Hu; Run Fang; Rende Ning (Inflammation Research, 2025)

Cassane diterpenoids with hepatic gluconeogenesis inhibitory activity from the seeds of Caesalpinia decapetala (Roth) Alston - De-Sheng Wang; Yu Shen; Lin-Fen Ding; Run-Cheng Yan; Ming Hu; Wen-Chao Tu; Liu-Dong Song; Suling Huang; Xing-De Wu (Phytochemistry, 2025)

Histological and molecular analysis of selenium synergistic RNAi of Dynamin gene in Bombyx mori - Run-Hui Ma; Ting-Ting Hong; Fei Hu; Kiran Thakur; Zhao-Jun Wei (Journal of Asia-Pacific Entomology, 2025)

High-precision geochronology of the Early Cretaceous Jiufotang Formation: Temporal constraints on the late phase of the Jehol Biota - Yu-Ting Zhong; Magdalena H. Huyskens; Run-Jian Chu; Han-Qing Yang; Jian-Fang Hu; Ya-Qiong Wang; Shi-Xi Cai; Qiong Wu; Qiang Ma; Huai-Chun Wu; Qing-Zhu Yin; Yi-Gang Xu (Earth and Planetary Science Letters, 2025)

Enhancement of polyethylene biodegradation by high-performance bacterial isolates - Hong Zhang; Fan Yang; Mengzong Hou; Run Hu; Lisha Song; Qiang Liu; Yanjiao Qi; Juanli Liu (Journal of Soils and Sediments, 2025)

Are smart cities advancing green development? A comprehensive analysis in China - Qinghong Cui; Run Chen; Xiancun Hu; Hongyun Si; Guangbin Wang (Sustainable Cities and Society, 2025)

The degradation of polyethylene by soil microbial communities was significantly enhanced through the Fe³ ⁺-induced Fenton-like reaction - Run Hu; Lisha Song; Huan Liu; Huaxian Tao; Yaohua Shi; Qiang Liu; Hong Zhang; Yanjiao Qi (Process Safety and Environmental Protection, 2025)

Bottom-up artificial construction of the M7-Z4 bacterial model enhanced sulfamethazine mineralization: Metagenomic analysis combined with bacterial isolation techniques - Mei Hu; Wenshan He; Run Jiang; Yan Zhang; Xiaohui Wang (Journal of Environmental Chemical Engineering, 2025)

Formation mechanisms of carcinogenic N-nitrosamines from dissolved organic matter derived from nitrogen-containing microplastics during chloramine disinfection - Run Zhou; Kecheng Zhu; Zhuo Gao; Xuemin Feng; Qian Hu; Lingyan Zhu (Water Research, 2025)

Target analysis of per- and polyfluoroalkyl substances in surface water: Occurrence, seasonal trends, and risk-based prioritization in the Minjiang River - Hui Zhang; Xin-Yue Wang; Yu-Hua Zheng; Jing-Run Hu; Xiao-Lin Li; Hong-Ling Yin; Rui Xiao; Xiao-Lan Zhu; Ting Chen; Huan Chen (Science of The Total Environment, 2025)

Identification and functional analysis of BAG gene family contributing to verticillium wilt resistance in upland cotton - Zhijuan Hu; Jingjie Yuan; Run Zou; Yilan Wang; Xuan Peng; Xingyong Yang; Chengjian Xie (Plant Science, 2025)

Characteristics and potential drivers of extreme high-temperature event frequency in Eurasia - Xiangqin Xie; Run Liu; Ruyuan Xiao; Sijia Hu; Caixian Huang; Yongze Bi; Yifan Xu (Dynamics of Atmospheres and Oceans, 2025)

Impact of the Madden-Julian oscillation on boreal autumn surface ozone in Guangdong Province, China - Sijia Hu; Run Liu; Caixian Huang; Xiangqin Xie; Yanxing Wu; Zheng Luo (Environmental Research, 2025)

Overexpression of CYP6CY1 is Involved in Imidacloprid Resistance in Sitobion miscanthi (Takahashi) (Homoptera: Aphidae) - Yun-Shan Xiong; Ling-Ling Cui; Gui-Lei Hu; Yu-Tai Jiang; Yong-Po Lv; Pei Zhang; Jin-Song Zheng; Bai-Zhong Zhang; Run-Qiang Liu (Neotropical Entomology, 2025)

Enhanced effect of ferrous sulfate on nitrogen retention and PBAT degradation during co-composting by combing with biochar-loaded FN1 bacterial composites - Long Cao; Linshan Wang; Yanjiao Qi; Shen Yang; Jiazhi Gao; Qiang Liu; Lisha Song; Run Hu; Zifan Wang; Hong Zhang (Journal of Environmental Management, 2025)

The link between eye movements and cognitive function in mild to moderate Alzheimer’s disease - Xiao-ting Ma; Lin-lin Yao; Shan-wen Liu; Xiao-fen Weng; Run-ying Bao; Yi-fan Yang; Yi-feng Li; Yan-yun Sun; Dan Xu; Zhen-yu Jia; Hua Hu (Experimental Brain Research, 2025)

Clock bias prediction of navigation satellite based on BWO-CNN-BiGRU-attention model - Wenlong Sun; Jinping Chen; Caibo Hu; Yongxin Lin; Maolei Wang; He Zhao; Run Zhao; Guitao Fu; Tan Zhao (GPS Solutions, 2025)

Anaerobic oxidation of methane coupled to reductive immobilization of hexavalent chromium by “Candidatus Methanoperedens” - Suicao Wang; Xueqin Zhang; Dihua Tian; Jing Zhao; Hesamoddin Rabiee; Fangrui Cai; Mengying Xie; Bernardino Virdis; Jianhua Guo; Zhiguo Yuan; Run Zhang; Shihu Hu (Journal of Hazardous Materials, 2024)

Promoting role of nitrogen-fixing bacteria and biochar on nitrogen retention and degradation of PBAT plastics during composting - Linshan Wang; Yanjiao Qi; Long Cao; Lisha Song; Run Hu; Qian Li; Yamin Zhao; Junyan Liu; Hong Zhang (Environmental Pollution, 2024)

In-situ and experimental investigations of the failure characteristics of surrounding rock through granites with biotite interlayers in a tunnel - Wei Zhang; Lei Hu; Zhi-Bin Yao; Yong-Run Xiong; Jun Zhao; Tao Ma; Song Chen; Zhe Xu (Engineering Geology, 2024)

Assessment of multidimensional diversity and conservation of threatened timber trees in China under climate change - Jian-Lin Hu; Xiu-Qin Ci; Xiao-Yan Zhang; Run Zhou; Jian-Hua Xiao; Zhi-Fang Liu; Can-Yu Zhang; Xuan Jin; Jie Li (Biological Conservation, 2024)

Overexpression of wheat C2H2 zinc finger protein transcription factor TaZAT8-5B enhances drought tolerance and root growth in Arabidopsis thaliana - Lulu Chen; Run Wang; Xiaoqing Hu; Dan Wang; Yuexia Wang; Ruili Xue; Mingzhu Wu; Hua Li (Planta, 2024)

Suppressed testicular macrophage M1 polarization by HDAC5 enforces insensitivity to LPS-elicited blood-testis barrier damage - Hao Li; Yi-Fan Hu; Xin-Run Wang; Kong-Wen Ouyang; Hua Wang; Kai-Wen Wang; Wei Chang; Jin Zhang; Zhi Yuan; Yong-Wei Xiong; Hua-Long Zhu; Lan Yang; et al. (Food and Chemical Toxicology, 2024)

Genome-wide analysis of long non-coding RNAs involved in the fruit development process of Cucumis melo Baogua - Ya-hui Li; Chun Liu; Run-zhe Xu; Yu-peng Fan; Ji-yuan Wang; Hu Li; Jian Zhang; Hui-jun Zhang; Jing-jing Wang; Da-kui Li (Physiology and Molecular Biology of Plants, 2024)

Strong concentration gradient effect and weak solvation effect in thermopower enhancement in K3Fe(CN)6/ K4Fe(CN)6 aqueous electrolyte with ethanol addition - Shouze Li; Zhou Li; Dongyan Xu; Run Hu (Chemical Engineering Journal, 2024)

Ultra-long room temperature phosphorescent materials based on tetraphenylethylene derivatives for anti-counterfeiting and encryption applications - Jian-Hang Hu; Run-Xin Hou; Chun Liu; Yan-Ping Wang; Yu-Fei Liu; Ying Huang; Zhu Tao; Xin Xiao (Chemical Engineering Journal, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Anti-pancreatic cancer activity of cassane diterpenoids isolated from the seeds of Caesalpinia sappan mediated by autophagy activation via ROS/AMPK/mTORC1 pathway - Jia Su; De-Sheng Wang; Guo-Xian Hu; Yu-Yao Liu; Ming Hu; Ya Chen; Qi-Qi Wang; Run-Cheng Yan; Yun Wu; Yong-Jiao Li; Ke Ma; Yan-Yan Qi; et al. (Phytochemistry, 2024)

microRNA-3037 targeting CYP6CY2 confers imidacloprid resistance to Sitobion miscanthi (Takahashi) - Bai-Zhong Zhang; Yu-Tai Jiang; Ling-Ling Cui; Gui-Lei Hu; Xin-An Li; Pei Zhang; Xiang Ji; Ping-Chuan Ma; Fan-Bin Kong; Run-Qiang Liu (Pesticide Biochemistry and Physiology, 2024)

Synergistically Augmenting Cancer Immunotherapy by Physical Manipulation of Pyroptosis Induction - Chenyang Zhao; Tingting Zheng; Run Wang; Xiaona Lin; Zhengming Hu; Zhuofei Zhao; Zhifei Dai; Desheng Sun (Phenomics, 2024)
Pyroptosis is a newly recognized type of programmed cell death mediated by the gasdermin family and caspase. It is characterized by the formation of inflammasomes and the following inflammatory responses. Recent studies have elucidated the value of pyroptosis induction in cancer treatment. The inflammatory cytokines produced during pyroptosis can trigger immune responses to suppress malignancy. Physical approaches for cancer treatment, including radiotherapy, light-based techniques (photodynamic and photothermal therapy), ultrasound-based techniques (sonodynamic therapy and focused ultrasound), and electricity-based techniques (irreversible electroporation and radiofrequency ablation), are effective in clinical application. Recent studies have reported that pyroptosis is involved in the treatment process of physical approaches. Manipulating pyroptosis using physical approaches can be utilized in combating cancer, according to recent studies. Pyroptosis-triggered immunotherapy can be combined with the original anti-tumor methods to achieve a synergistic therapy and improve the therapeutic effect. Studies have also revealed that enhancing pyroptosis may increase the sensitivity of cancer cells to some physical approaches. Herein, we present a comprehensive review of the literature focusing on the associations between pyroptosis and various physical approaches for cancer and its underlying mechanisms. We also discussed the role of pyroptosis-triggered immunotherapy in the treatment process of physical manipulation.

Indole-3-acetic acid improves periphyton's resistance to ultraviolet-B: From physiological-biochemical properties and bacteria community to livestock-polluted water purification - Tianyu Shi; Maobulin Lure; Run Zhang; Zhiheng Liu; Qianming Hu; Jia Liu; Shengtao Yang; Liandong Jing (Environmental Research, 2024)

Biomimetic hierarchical composites inspired by natural pomelo peel for mechanical-damage resistance and storage of fruits - Run-Ze Hu; Lei Liu; En-Jiang Liu; Jie Tu; Xiao-Hui Yao; Peng Song; Dong-Yang Zhang; Zhan-Hua Huang; Tao Chen (Chemical Engineering Journal, 2024)

Impacts of compound extreme weather events on summer ozone in the Beijing-Tianjin-Hebei region - Peilan Lu; Run Liu; Zheng Luo; Shiyi Li; Yanxing Wu; Wenzhao Hu; Xin Xue (Atmospheric Pollution Research, 2024)

Anomalous high ozone in the Pearl River Delta, China in 2019: A cause attribution analysis - Yanxing Wu; Run Liu; Jianmin Xu; Wenzhao Hu; Shaw Chen Liu (Atmospheric Environment, 2024)

Green N1 additive modified perovskite precursor enables effective manufacturing of large-area solar cell modules with high efficiency and stability - Yue Zang; Yibo Tu; Chuanjia Jiao; Wangnan Li; Peng Zhou; Jiahao Cheng; Gaoyuan Yang; Tianxiang Shao; Jingchuan Ye; Guodong Li; Liang Chu; Shaojian Lu; et al. (Chemical Engineering Journal, 2024)

Soil aggregate-associated organic carbon mineralization and its driving factors in rhizosphere soil - Jun-Ya Li; Peng Chen; Zhi-Guo Li; Lin-Yang Li; Run-Qin Zhang; Wei Hu; Yi Liu (Soil Biology and Biochemistry, 2023)

The way to elastic ferroelectrics - Ben-Lin Hu; Brahim Dkhil; Run-Wei Li (Science Bulletin, 2023)

Continuous Co-incorporation of Chinese Milk Vetch and Rice Straw with Reduced Chemical Fertilizer Maintains Rice Yield as a Consequence of Increased Carbon and Nitrogen Storage in Soil Aggregates - Rongyan Bu; Wenlong Cheng; Shang Han; Run Hu; Hui Wang; Shan Tang; Min Li; Qin Zhu; Ji Wu; Weidong Cao (Journal of Soil Science and Plant Nutrition, 2023)

Bed level changes in the surf zone during post-storm beach recovery - Pengpeng Hu; Zhiqiang Li; Chunhua Zeng; Daoheng Zhu; Run Liu; Qianxin Su; Jieping Tang; Yamin Zhu (Frontiers in Marine Science, 2023)
The study of post-storm beach recovery is important for economic development and the protection of life in coastal areas. In this study, field observations were conducted for 21 days in the surf zone of Dongdao Beach, Hailing Island, China, after tropical storm “Cempaka”. Data on depth, wave, Eulerian velocity, sediment, three-dimensional topography of the beach, and high-frequency variations in bed-level elevation were collected. The results showed that the beach experienced medium- to low- to medium-energy waves during field observations and covered two complete astronomical tide cycles. Contrary to the effect of wave energy conditions on beaches under normal wave conditions, a higher wave energy during beach recovery can promote silting and accelerate beach recovery. Tidal water level is an important factor affecting beach restoration, and a smaller tidal range is conducive to beach accretion. In a mixed semidiurnal tide, beach erosion and accretion occurred in the “highest tide” and “sub-highest tide” tidal cycles, respectively, and the combined effect of the two affected the change in the bed level in a mixed semidiurnal tide. After the storm, the hydrodynamic forcing mechanism and self-organization process of the sand bar jointly drove the formation of the topography of the bar channel in the surf zone. After the storm stopped, the spectral energy in free surface elevation was mainly distributed in the very low frequency and decayed rapidly at the infragravity band. The very low-frequency pulsation of the surf zone during recovery is a prominent feature of bed-level elevation, depth, and velocity. This study provides a good case for the study of hydrodynamic and bed level changes in the post-storm surf zone, as well as a reference for future studies of the intrinsic mechanisms post-storm beach recovery processes around the world.

Micro-mechanism insights into the adsorption of anionic dyes using quaternary ammonium-functionalised chitosan aerogels - Nan Du; Li-Yuan Huang; Yan-Shu Xiong; Run Tian; Jiang-Yu Yin; Dan-Yu Cao; Dong-Bin Hu; Hai-Qin Lu; Wen Li; Kai Li (Carbohydrate Polymers, 2023)

Processes conducive to high ozone formation in Pearl River Delta in the presence of Pacific tropical cyclones - Wenzhao Hu; Run Liu; Zichao Chen; Shanshan Ouyang; Tingting Hu; Yao Wang; Zhenyuan Cui; Bin Jiang; Duohong Chen; Shaw Chen Liu (Atmospheric Environment, 2023)

Air pollution, alcohol consumption, and the risk of elevated liver enzyme levels: a cross-sectional study in the UK Biobank - Run Liu; Dankang Li; Junqing Xie; Lulin Wang; Yonghua Hu; Yaohua Tian (Environmental Science and Pollution Research, 2023)

Facile, green and scalable preparation of low-cost PET-PVDF felts for oil absorption and oil/water separation - Ming Hao; Tianyi Zhang; Xiaodong Hu; Zhijun Chen; Bo Yang; Xiaoxiao Wang; Yanbo Liu; Run Wang; Yong Liu (Journal of Hazardous Materials, 2023)

Variations in the concentration, source and flux of polycyclic aromatic hydrocarbons in sediments of the Pearl River Estuary: Implications for anthropogenic impacts - Yali Li; Nairong Guo; Ke Yuan; Baowei Chen; Junjie Wang; Maofeng Hua; Jing Yu; Jingyan Hu; Run Lu; Shichun Zou; Ying Yang (Science of The Total Environment, 2023)

Biotransformation of sulfamonomethoxine in a granular sludge system: Pathways and mechanisms - Meng-Yuan Li; Run-Dong Zhang; Yi-Xing Lin; Qi-Wen Li; Qiu-Yue Zhao; Zong-Xi Zhao; Zhong-Ming Ling; Long-Fei Shu; Min Zhang; Li-Xin Hu; Yi-Jing Shi; Guang-Guo Ying (Chemosphere, 2023)

Non-destructive characterization of proton diffusion coefficient within live electroactive biofilm - Linbin Hu; Run Liu; Yang Yang; Qian Fu; Liang Zhang; Xun Zhu; Qiang Liao; Jun Li (Chemical Engineering Journal, 2023)

Effect of enhanced UV-B radiation on growth and photosynthetic physiology of Iris tectorum maxim - Run Chu; Qin-hu Zhang; Yu-zhen Wei (Photosynthesis Research, 2022)

The local ecological knowledge of butterfly diversity is derived from utilitarian purposes in Southwest China’s biodiversity hotspot - Run-Ming Yang; Shao-Ji Hu; Benjamin D. Blanchard; Akihiro Nakamura (Biodiversity and Conservation, 2022)

Apatite chemistry as a petrogenetic–metallogenic indicator for skarn ore-related granitoids: an example from the Daye Fe–Cu–(Au–Mo–W) district, Eastern China - Run-Jie Zhou; Guang Wen; Jian-Wei Li; Shao-Yong Jiang; Hao Hu; Xiao-Dong Deng; Xin-Fu Zhao; Dai-Rong Yan; Ke-Tao Wei; Heng-An Cai; Shi-Chao Shang; Bai-Cun Li; et al. (Contributions to Mineralogy and Petrology, 2022)

The decreased expression of GW2 homologous genes contributed to the increased grain width and thousand‑grain weight in wheat-Dasypyrum villosum 6VS·6DL translocation lines - Zhiyu Feng; Long Song; Wanjun Song; Zhongqi Qi; Jun Yuan; Run Li; Haiming Han; Huifang Wang; Zhaoyan Chen; Weilong Guo; Mingming Xin; Jie Liu; et al. (Theoretical and Applied Genetics, 2021)

Prediction and Identification of Epitopes in the Emy162 Antigen of Echinococcus multilocularis - Ming-Quan Pang; Feng Tang; Hai-Jiu Wang; Ying Zhou; Li Ren; Run-Le Li; Hu Zhou; Chen-Fei Wan; Chuan-Chuan Liu; Cai-Rang Yangdan; Hai-Ning Fan (Acta Parasitologica, 2020)

DNMT3A controls miR-200b in cardiac fibroblast autophagy and cardiac fibrosis - Xu-Dong Zhao; Run-He Qin; Jing-Jing Yang; Sheng-Song Xu; Hui Tao; Xuan-Sheng Ding; Kai-Hu Shi (Inflammation Research, 2018)

Accumulation of freshwater in the permanent ice zone of the Canada Basin during summer 2008 - Jinlu Tong; Min Chen; Weifeng Yang; Run Zhang; Hong Pan; Minfang Zheng; Yusheng Qiu; Wangjiang Hu; Jian Zeng (Acta Oceanologica Sinica, 2017)

A catastrophic debris flow in the Wenchuan Earthquake area, July 2013: characteristics, formation, and risk reduction - Tao Hu; Run-qiu Huang (Journal of Mountain Science, 2017)

A Brachypodium distachyon MAPKK Gene BdMKK6.2 Negatively Regulates Drought Stress Tolerance in Transgenic Tobacco Plants - Jiutong Sun; Run Zhou; Yaping Li; Wei Hu; Ding Qiu; Xiatian Wang; Qiong Wang; Zhijuan Feng; Lianzhe Wang; Yi Zhou; Guangyuan He; Guangxiao Yang (Journal of Plant Growth Regulation, 2016)

The Brachypodium distachyon BdWRKY36 gene confers tolerance to drought stress in transgenic tobacco plants - Jiutong Sun; Wei Hu; Run Zhou; Lianzhe Wang; Xiatian Wang; Qiong Wang; Zhijuan Feng; Yaping Li; Ding Qiu; Guangyuan He; Guangxiao Yang (Plant Cell Reports, 2015)

Low 210Pb in the upper thermocline in the Canadian Basin: scavenge process over the Chukchi Sea - Wangjiang Hu; Min Chen; Weifeng Yang; Run Zhang; Yusheng Qiu; Minfang Zheng (Acta Oceanologica Sinica, 2014)

Two new coumarins from Edgeworthia chrysantha - Xiao-Jia Hu; Hui-Zi Jin; Wei-Dong Zhang; Wei Zhang; Shi-Kai Yan; Run-Hui Liu; Yun-Heng Shen; Wen-Zheng Xu (Natural Product Research, 2009)

Population genetic structure of the melon fly, Bactrocera cucurbitae (Diptera: Tephritidae), from China and Southeast Asia - Jian Hu; Jun L. Zhang; Francesco Nardi; Run J. Zhang (Genetica, 2008)

Inhibiting effect of vagal nerve stimulation to seizures in epileptic process of rats - Hong-Jun Yang; Kai-Run Peng; San-Jue Hu; Yan Liu (Neuroscience Bulletin, 2007)